2013
DOI: 10.1093/brain/aws327
|View full text |Cite
|
Sign up to set email alerts
|

Diverging patterns of amyloid deposition and hypometabolism in clinical variants of probable Alzheimer’s disease

Abstract: The factors driving clinical heterogeneity in Alzheimer's disease are not well understood. This study assessed the relationship between amyloid deposition, glucose metabolism and clinical phenotype in Alzheimer's disease, and investigated how these relate to the involvement of functional networks. The study included 17 patients with early-onset Alzheimer's disease (age at onset <65 years), 12 patients with logopenic variant primary progressive aphasia and 13 patients with posterior cortical atrophy [whole Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
242
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 286 publications
(275 citation statements)
references
References 94 publications
30
242
0
3
Order By: Relevance
“…Maps of cerebral metabolic rate for glucose (CMRgl) were obtained from FDG‐PET images preprocessed at the University of California – Berkeley, following a standardized procedure described previously 41. Briefly, FDG‐PET frames were summed and standard uptake volume ratios (SUVR) were calculated by normalizing the summed FDG image to mean activity in the pons for each subject 42…”
Section: Methodsmentioning
confidence: 99%
“…Maps of cerebral metabolic rate for glucose (CMRgl) were obtained from FDG‐PET images preprocessed at the University of California – Berkeley, following a standardized procedure described previously 41. Briefly, FDG‐PET frames were summed and standard uptake volume ratios (SUVR) were calculated by normalizing the summed FDG image to mean activity in the pons for each subject 42…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, FDG-PET is also highly useful in differentiating within amyloid-positive subtypes of disease which cannot be distinguished on the basis of their amyloid PET-scan. This includes Lewy-body dementia, posterior cortical atrophy, and the logopenic variant of progressive aphasia [255,261]. A tight correlation between the level of metabolic decline with the degree of cognitive impairment has been demonstrated consistently [262], which qualifies this method for follow-up and therapy control studies [263].…”
Section: Fluorodeoxyglucose-petmentioning
confidence: 95%
“…Thus, amyloid-imaging may not be able to differentiate between Lewy-body dementia and AD. Furthermore, amyloidimaging alone may not be helpful with regard to distinguishing between amyloid-positive subtypes of AD (typical AD, logopenic variant of progressive aphasia, and posterior cortical atrophy) [261]. With regard to early diagnosis, a number of studies demonstrated a high predictive value of a positive amyloid-scan in the stage of MCI with regard to conversion to AD [275,276].…”
Section: Amyloid-pet Imagingmentioning
confidence: 99%
“…With noninvasive PET biomarkers, such as Pittsburgh compound B ( 11 C-PiB) and 18 F-FDG, AD-related pathologies, namely fibrillary amyloid burden and hypometabolism, as well as their longitudinal alterations and associations can be investigated in vivo. Compared with healthy subjects, AD patients show specific patterns of reduced 18 F-FDG metabolism, as a measure for neuronal dysfunction (4), and increased amyloid deposition (5-7), which are highly overlapping especially in the posterior cingulate cortex (PCC) and parietal and temporal cortical areas (8).…”
mentioning
confidence: 99%